Clinical significance of T cell receptor excision circle (TREC) quantitation after allogenic HSCT - Mikhael, Neveen Lewis (Blood Res, 2019)
BACKGROUND: Hematopoietic stem cell transplantation (HSCT) is a well-established treatment modality for a variety of diseases. Immune reconstitution is an important event that determines outcomes. The immune recovery of T cells relies on peripheral expansion of mature graft cells, followed by differentiation of donor-derived hematopoietic stem cells. The formation of new T cells occurs in the thymus and as a byproduct, T cell receptor excision circles (TRECs) are released. Detection of TRECs by PCR is a reliable method for estimating the amount of newly formed T cells in the circulation and, indirectly, for estimating thymic function. The aim of this study was to determine the role of TREC quantitation in predicting outcomes of human leucocyte antigen (HLA) identical allogenic HSCT. METHODS: The study was conducted on 100 patients receiving allogenic HSCT from an HLA identical sibling. TREC quantification was done by real time PCR using a standard curve. RESULTS: TREC levels were inversely related to age (P=0.005) and were significantly lower in patients with malignant diseases than in those with benign diseases (P=0.038). TREC levels could predict relapse as an outcome but not graft versus host disease (GvHD) and infections. CONCLUSION: Age and nature of disease determine the TREC levels, which are related to relapse.